Inhibitory Effect of Aqueous Salvia officinalis’s leaves in the Growth of Candida albicans from Infected Women with Vaginal Candidiasis - jasim, Rusul Mohammad; Abd AL-khaliq, Israa Mohammad (AL-Kindy College Medical Journal, 2011)
Background: Salvia officinalis is a plant belong toLabiatae family .The common name of Salvia is sagewhich mean save. The leaves of Salvia have specialoil which is effective against filamentous fungi andyeasts such as Candida albicans which is thecausative agent of vaginal candidiasis in womenMethods. Cultures from 50 swabs of Candidaalbicans isolated from vagina of 70 patient womenwho complains from vaginal problems, their ages(24-43) years from Central City Hospital duringFebreoury 2009 to April 2009 were cultured onSabouraud Dextrose Agar (SDA) .Nystatin was usedas positive reference standard to determine thesensitivity of this fungus . and less this concentrationthere was no minimum inhibition for the CandidaResults: The aqueous extract of Salvia officinalis atvarious concentrations inhibited the growth of C.Albicans . This inhibitions reached to a maximum of100% for extract at 25 mg / ml and the minimuminhibition was 170 mm at 15 mg /ml for the extract .While the minimum and maximum inhibition fornystatin was at 50 μg/ml,and less concentration. Therewas no minimum inhibition for the CandidaConclutions : The findings provide support for theuse of this plant in traditional medicine for fungalinfections especially against candidiasis .